Strategi Pemasaran Usaha Mikro, Kecil, dan Menengah (UMKM) melalui Digitalisasi Marketing untuk Branding Desa - Sundari, Ariefah (Prapanca : Jurnal Abdimas, 2024)
Marketing strategy for micro, small, and medium enterprises (MSME) through digitalization Mrketing for Village branding in Ngadipuro Village, Widang District, Tuban Regency. The marketing strategy carried out in developing a MSME product in Ngadipuro village is by utilizing the digital system, by following the times, we will provide solutins to various kinds of problems faced by partners. Whit this, the steps that we carry out firs are surveys of MSME owners, what MSME are in Ngadipuro village, then we hold a socialization regarding marketing strategies that can be done in this day and age, and the final action we take is to assist partners, here we only take MSME that we think are core, namely crackers, soy milk, corn chips, turmeric asem and Goat Farming. In this case, we help to provide a means of promoting an item.